Modelling and Controller Design of Electro-Pneumatic Actuator Based on PWM - Behrouz Najjari; S. Masoud Barakati; Ali Mohammadi; Mohammad Javad Fotuhi; Saeid Farahat; Mohammad Bostanian (IAES International Journal of Robotics and Automation (IJRA), 2012)
In this paper, a nonlinear model associated to the fast switching on-off solenoid valve and pneumatic cylinder was dynamically presented. Furthermore, an investigation into the electrical, magnetic, mechanical and fluid subsystems are made. Twocommon control policies to track valve position, a Proportional Integrator (PI) based on Pulse Width Modulation (PWM) and hysteresis controllers, are investigated. To control cylinder position, a Programmable Logic Controller (PLC) on a simulated unit and an experimental setup regulated with AVR microcontroller are carried out. Experimental results show effective validation to the simulation results from PLC. DOI: http://dx.doi.org/10.11591/ijra.v1i3.565